(‐)‐Epigallocatechin‐3‐Gallate Antihyperalgesic Effect Associates With Reduced CX3CL1 Chemokine Expression in Spinal Cord. (29th November 2016) - Bosch‐Mola, Marc; Homs, Judit; Álvarez‐Pérez, Beltrán; Puig, Teresa; Reina, Francisco; Verdú, Enrique; Boadas‐Vaello, Pere
Abstract : (‐)‐Epigallocatechin‐3‐gallate (EGCG) is a major polyphenol in green tea with beneficial effects on the neuropathic pain alleviation in animal models. Because chemokine fractalkine (CX3CL1) has been suggested as an important signal during neuropathic pain development, this study aimed to investigate whether CX3CL1 expression may be modulated by EGCG treatment reducing hyperalgesia in chronic constriction injured mice. To this end, Balb/c mice were subjected to a chronic constriction injury of sciatic nerve (CCI) and treated with EGCG or vehicle once a day during the first week following surgery. Thermal hyperalgesia was tested at 7 and 14 days post‐surgery, and the expression of CX3CL1 and its mRNA were analyzed in spinal cord at the end of the experimental period. Results revealed that EGCG treatment significantly reduced thermal hyperalgesia in CCI‐injured mice at short time, and this antihyperalgesic effect was associated with a down‐regulation of CX3CL1 protein expression in the spinal cord. On the other hand, EGCG treatment did not affect the CX3CL1 transcription. Overall, our results suggest a new role of EGCG‐treatment in an experimental model of neuropathic pain as a mediator of nociceptive signaling cross talk between neurons and glial cells in the dorsal horn of the spinal cord. Copyright © 2016 John Wiley & Sons, Ltd.